Who Stays in Rural Nursing Practice? An International Review of the Literature on Factors Influencing Rural Nurse Retention - Candice Manahan Roberge (Online Journal of Rural Nursing and Health Care, 2012)
This paper explores factors that influence rural nurse retention. A comprehensive literature review was used to highlight, examine and evaluate studies that identify factors, including personal characteristics and experiences, in relation to rural nurse retention and job satisfaction. The findings from the literature review suggest rural nurse retention is influenced by level of job satisfaction. The findings also suggest factors, including personal characteristics and experiences, influence job satisfaction. The literature review findings further indicate factors, including personal characteristics and experiences, affect the duration of rural nurse practice. The current rural nursing retention strategies in British Columbia are explored. Based on the findings from the literature review, detailed recommendations for future research and recommendations for rural nursing retention strategies are made. The concepts identified inform health human resources retention strategies, specifically nursing retention in rural areas.